Descripción osteológica del rorcual común (Balaenoptera physalus, Linnaeus, 1758) del Museo de Ciencias Naturales de Barcelona - Carrillo, M.; Alcántara, E.; Taverna, A; Paredes, R.; Garcia-Franquesa, E. (Museu de Ciències Naturals de Barcelona, 2014)
Description of the skeleton of the fin whale (Balaenoptera physalus, Linnaeus, 1758) at the Natural History Museum of Barcelona We describe the osteology of the fin whale (Balaenoptera physalus, L., registration code MZB 83-308) at the Natural History Museum of Barcelona. The specimen was stranded and died on a beach in Llançà (Girona, Spain) in 1862. The skeleton weighed 1,161.59 kg and measured 14. 6 m, although the live animal would have been longer because the invertebral tissue was not included in the length originally stated. The newly reconstructed skeleton includes the invertebral discs and is 17.5 m long. The skull weighs 484 kg and the condilobasal length is 431 cm ( 24. 84% of the total length), corresponding to the mean length of specimens in the Mediterranean. The vertebral column has 58 vertebra structured following the formula: C7 T14 L14 Cd23. It is 10.29 m long and weighs 470.95 kg. All the cervical vertebra are free and show dorsoventral compression, differing from the thoracic, lumbar and first caudal vertebra that are relatively uniform, and rounded. From Cd14 se onwards, the vertebra vary in shape and the relationship between width and height is greater than 1, indicating lateral compression. The lack of suture lines in the epiphysis of the ulna and radius indicates the specimen is an adult that has reached ossification maturation.